Stress Analysis of Reinforced Concrete Dam under Basic Loads and Earthquakes (Proceedings of Faculty of Civil Engineering, 2022)
In this paper, the dimensioning of a high massive reinforced concrete dam according to the conditions of general structural stability was performed. The values of normal stresses in the dam body were calculated by an analytical procedure. A comparison was performed with the results of stress values obtained by numerical analysis in the SAP2000 software. Three load combinations for two foundation rock types were tested. A stronger correlation of numerical and analytical results was observed in the case of the foundation on harder rock.
Keywords: dam; analytical model; numerical model; rock; earthquake